2016
DOI: 10.1161/circulationaha.115.018443
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Fast-Slow Atrioventricular Nodal Reentrant Tachycardia Incorporating a “Superior” Slow Pathway

Abstract: Background— The existence of an atypical fast-slow (F/S) atrioventricular nodal reentrant tachycardia (AVNRT) including a superior (sup) pathway with slow conductive properties and an atrial exit near the His bundle has not been confirmed. Methods and Results— We studied 6 women and 2 men (age, 74±7 years) with sup-F/S-AVNRT who underwent successful radiofrequency ablation near the His bundle. Programmed ventricular stimulation induced retrograde conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 31 publications
(36 reference statements)
3
79
0
Order By: Relevance
“…A sup‐F/S‐AVNRT is a rare subtype of F/S AVNRT, with a site of earliest atrial activation located in the anteroseptal region near the HBE, and the superior SP is used as the retrograde limb on the reentrant circuit. Ablation could be successfully performed for tachycardia from the right atrial anteroseptal region, posterior to the HBE recording site, or from the noncoronary sinus of Valsalva without atrioventricular block . In the present case, retrograde superior SP was not observed during RV programmed stimulation at baseline.…”
Section: Commentarymentioning
confidence: 55%
See 4 more Smart Citations
“…A sup‐F/S‐AVNRT is a rare subtype of F/S AVNRT, with a site of earliest atrial activation located in the anteroseptal region near the HBE, and the superior SP is used as the retrograde limb on the reentrant circuit. Ablation could be successfully performed for tachycardia from the right atrial anteroseptal region, posterior to the HBE recording site, or from the noncoronary sinus of Valsalva without atrioventricular block . In the present case, retrograde superior SP was not observed during RV programmed stimulation at baseline.…”
Section: Commentarymentioning
confidence: 55%
“…However, the orthodromic AVRT was unlikely because RV overdrive pacing did not entrain the tachycardia other than the last RV pacing (Figure A). Furthermore, previous studies reported that the ventriculoatrial dissociation was characteristic of the sup‐F/S‐AVNRT and may be attributed to the lower common pathway …”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations